2020
DOI: 10.1039/d0bm00599a
|View full text |Cite
|
Sign up to set email alerts
|

Bioinorganic supplementation of calcium phosphate-based bone substitutes to improvein vivoperformance: a systematic review and meta-analysis of animal studies

Abstract: Supplementation of CaP-based bone substitutes with bioinorganics affects biological performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 144 publications
1
14
0
Order By: Relevance
“…CP cement can be classified into different groups with different stability and/or solubility: (1) HA and α-tricalcium phosphate (α-TCP); (2) BCP, and (3) DCPD and β-tricalcium phosphate (β-TCP) [ 28 ]. Table 1 lists the main calcium phosphate compounds used as bone substitutes and their Ca/P ratio [ 29 ] ( Table 1 ).…”
Section: Calcium Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…CP cement can be classified into different groups with different stability and/or solubility: (1) HA and α-tricalcium phosphate (α-TCP); (2) BCP, and (3) DCPD and β-tricalcium phosphate (β-TCP) [ 28 ]. Table 1 lists the main calcium phosphate compounds used as bone substitutes and their Ca/P ratio [ 29 ] ( Table 1 ).…”
Section: Calcium Compoundsmentioning
confidence: 99%
“…A recent meta-analysis of in-vitro studies reported that strontium, magnesium, and silica significantly enhanced new bone formation, while zinc did not have any effect. Moreover, strontium significantly enhanced and silicon inhibited CP cement degradation, while other bioinorganic supplementations generally did not promote material degradation at all [ 29 ].…”
Section: Calcium Compoundsmentioning
confidence: 99%
“…Nanosized HA also receives the name HA nanoparticles and possesses a grain size of less than 100 nm in at least one dimension. HA nanoparticles display a high surface area and a fine nanostructure, close to that of the mineral discovered in hard tissues [10]. Indeed, the bioceramics which rapidly stimulate osteointegration and bone tissue generation are those that imitate the composition and structure of the bone mineral.…”
Section: Introductionmentioning
confidence: 95%
“…Positive effects of Sr on osteoporosis and osteoarthritis were reported. [22,23] One of the important properties of Sr, causing a high interest in materials research, is its osteoinductivity. Sr has a dual effect on bone remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…[38,39] In the case of Sr-DCPD, there is a cumulative effect of Sr on osteogenesis and a higher rate of DCPD bioresorption compared to HA cements. [23] As a precursor for the brushite cements preparation, β-tricalcium phosphate (β-TCP, β-Ca 3 (PO 4 ) 2 ) or, in this case, Sr-β-TCP, [40] is mainly used. A number of studies were devoted to Sr-substituted brushite cements.…”
Section: Introductionmentioning
confidence: 99%